An F-Actin Mega-Cable Is Associated With the Migration of the Sperm Nucleus During the Fertilization of the Polarity-Inverted Central Cell of Agave inaequidens - González-Gutiérrez, Alejandra G.; Gutiérrez-Mora, Antonia; Verdín, Jorge; Rodríguez-Garay, Benjamín (Frontiers in Plant Science, 2021)
Asparagaceae´s large embryo sacs display a central cell nucleus polarized toward the chalaza, which means the sperm nucleus that fuses it during double fertilization migrates an atypical long distance before karyogamy. Because of the size and inverted polarity of the central cell in Asparagaceae, we hypothesize that the second fertilization process is supported by an F-actin machinery different from the short-range F-actin structures observed in Arabidopsis and other plant models. Here, we analyzed the F-actin dynamics of Agave inaequidens, a classical Asparagaceae, before, during, and after the central cell fertilization. Several parallel F-actin cables emerged from the central cell nucleus, enclosing the vacuole, and reaching the micropylar pole were observed. As fertilization progressed, a thick F-actin mega-cable traversing the vacuole appeared, connecting the central cell nucleus with the micropylar pole near the egg cell. This mega-cable wrapped the sperm nucleus in transit to fuse the central cell one. Once karyogamy finished, the mega-cable disassembled, but new F-actin structures formed during the endosperm development. These observations suggest that Asparagaceae, and probably other plant species with similar embryo sacs, evolved an F-actin machinery specifically adapted to support the migration of the fertilizing sperm nucleus within a large-sized and polarity-inverted central cell.